VOLUNTARIADO EM UMA ORGANIZAÇÃO DE SERVIÇOS: DISCUSSÃO DA EXPERIÊNCIA PAPAI NOEL DOS CORREIOS DE IJUÍ/RS - Porciuncula, Juliana; Teixeira, Enise B.; Toso, Vanessa C. (Salão do Conhecimento, 2013)
Resumo